2023
DOI: 10.1088/1361-6579/acc3d6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body position change on noninvasively acquired intracranial pulse waves

Abstract: Objective. Craniospinal compliance (CC) is an important metric for the characterization of space-occupying neurological pathologies. CC is obtained using invasive procedures that carry risks for the patients. Therefore, noninvasive methods for acquiring surrogates of CC have been proposed, most recently based on changes in the head’s dielectric properties during the cardiac cycle. Here, we have tested whether changes in body position, which are known to influence CC, are reflected in a capacitively acquired si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Computerized noninvasive ICP monitoring was reported by [41,42]. In recent years, a few ICP pulse wave analysis publications have appeared, such as a patent [43], a device [17], a calculation of the P2/P1 ratio [18], and a device for measuring the head's dielectric properties (Cephalotec, Horgen, Switzerland), which is changing as a heartbeat-related pulse wave [44]. None of them performed comparative pulse wave morphology analyses, as we presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized noninvasive ICP monitoring was reported by [41,42]. In recent years, a few ICP pulse wave analysis publications have appeared, such as a patent [43], a device [17], a calculation of the P2/P1 ratio [18], and a device for measuring the head's dielectric properties (Cephalotec, Horgen, Switzerland), which is changing as a heartbeat-related pulse wave [44]. None of them performed comparative pulse wave morphology analyses, as we presented here.…”
Section: Discussionmentioning
confidence: 99%
“…A modeling study confirmed that changes in the dielectric properties of the head correlate to the cardiac and respiratory cycles associated with changes in the volumes of cerebral blood and CSF (Karimi et al 2023). The signal provided by the device, denoted W, was shown through experimental hyperventilation studies to be, at least partially, of intracranial origin (Spiegelberg et al 2023) and the amplitude of its cardiac-related oscillations was demonstrated to change during head-up and head-down tilt testing in a way that reflects the alterations in blood and CSF volume induced by changes in body position (Boraschi et al 2023). The authors concluded that W may therefore contain meaningful information on craniospinal compliance; however, they have not yet reported comparative analyses between invasive and noninvasive methods of compliance assessment.…”
Section: Noninvasive Icp Pulse Waveform Estimationmentioning
confidence: 99%
“…Most recently, an approach based on the capacitive measurement of the dielectric properties of the head was introduced 13 . This method has been investigated so far only on young healthy volunteers below the age of 30 14 . Given that ageing affects the cerebrospinal fluid (CSF) system, for example by decreasing ICP 15 17 , it is expected that also the dielectric properties of the head change with age.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown through hyperventilation testing on healthy volunteers that W is, at least in part, of intracranial origin 13 . The peak-to-valley amplitude (AMP) of W associated with cardiovascular activity has been shown to decrease with head-up tilting and increase with head-down tilting in healthy subjects below the age of 30 14 . Tilt testing is a noninvasive maneuver known to change the relative contributions of the cranial and spinal compartments to CC 19 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation